Ferroptosis exacerbates the clonal deletion of virus-specific exhausted CD8+ T cells - Tian, Qin; Chen, Cheng; Lu, Jinjin; Zheng, Xinyu; Zhai, Xiuming; Yang, Yanping; Zhao, Ziyao; Hao, Jiangtao; Yang, Ke; Ye, Lilin; Wang, Yifei (Frontiers in Immunology, 2024)
During chronic infection or tumorigenesis, persistent antigen stimulation contributes to the exhaustion of CD8+ T cells. Nevertheless, exhausted CD8+ T (TEX) cells still preserve certain effector function, and maintaining a reservoir of exhausted cells is of vital importance for virus elimination and tumor eradiation. Despite considerable work interrogating the rejuvenation of TEX cells, mechanisms underpinning the clonal deletion of TEX cells remain largely unexplored over the past decade. In this study, we employed mouse models of LCMV infection to demonstrate that excessive accumulation of lipid peroxidation rendered virus-specific TEX cells to ferroptosis, which may correlate with enhanced mitochondria-derived oxidative stress and compromised activity of glutathione peroxidase 4 (GPX4). In addition, either incomplete or complete ablation of GPX4 resulted in exacerbated ferroptosis and aggravated shrunken population of virus-specific TEX cells. On the other hand, inhibiting ferroptosis via administration of a ferroptosis inhibitor or overexpression of GPX4 greatly rectified the cell loss of virus-specific TEX cells. Collectively, we disclosed ferroptosis as a crucial player in the clonal deletion of virus-specific TEX cells and stressed the intervention of ferroptosis as a promising approach to optimize the longevity of virus-specific TEX cells.